2021
DOI: 10.1101/2021.03.17.435863
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutational escape from the polyclonal antibody response to SARS-CoV-2 infection is largely shaped by a single class of antibodies

Abstract: Monoclonal antibodies targeting a variety of epitopes have been isolated from individuals previously infected with SARS-CoV-2, but the relative contributions of these different antibody classes to the polyclonal response remains unclear. Here we use a yeast-display system to map all mutations to the viral spike receptor-binding domain (RBD) that escape binding by representatives of three potently neutralizing classes of anti-RBD antibodies with high-resolution structures. We compare the antibody-escape maps to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 61 publications
(194 reference statements)
7
69
2
Order By: Relevance
“…We note that our antibody binding-escape maps generated in prior studies have proven highly concordant with the effects of mutations on the antibody neutralization of mutant spike-pseudotyped viral particles. 15,18,32,33 Importantly, the conclusions of our work that are the most immediately relevant to clinical antibody use have been independently verified by pseudovirus neutralization assays. Specifically, as indicated in Figure 1B, Wang et al 14 confirmed that E484K and K417N abolish neutralization by LY-CoV555 and LY-CoV016, respectively.…”
Section: Limitations Of Studymentioning
confidence: 56%
“…We note that our antibody binding-escape maps generated in prior studies have proven highly concordant with the effects of mutations on the antibody neutralization of mutant spike-pseudotyped viral particles. 15,18,32,33 Importantly, the conclusions of our work that are the most immediately relevant to clinical antibody use have been independently verified by pseudovirus neutralization assays. Specifically, as indicated in Figure 1B, Wang et al 14 confirmed that E484K and K417N abolish neutralization by LY-CoV555 and LY-CoV016, respectively.…”
Section: Limitations Of Studymentioning
confidence: 56%
“…This region has been previously implicated in antibody escape [35] ). This residue may be therefore part of an epitope recognized by class 1 antibodies, whose neutralizing activity is escaped by the two aforementioned VOCs [22,26]. On the other hand, N450 is also involved in the surface of interaction between the RBD and some monoclonal antibodies [45]; moreover, in a deep mutational scanning experiment, the mutation N450K determined a mild increase in ACE2 binding [28].…”
Section: Resultsmentioning
confidence: 99%
“…The former one is now found in a number of other emerging lineages and it has been identified as a major player in antibody escape, due to its presence in a major epitope recognized by class II RBD-directed antibodies [26][27][28]. K417 on the other hand is located in an epitope recognized by class I antibodies, and is thought to provide a minor contribution to polyclonal antibody response escape [26] and to possibly stabilize, together with E484K and N501Y, the interaction between the RBD and the ACE 2 receptor [15]. The trends of new infections connected with these VOCs and other emerging variants of interest (VOIs) are being closely monitored due to the possible negative impact they might have on massive vaccination campaigns [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…These results could be recapitulated in experiments with SARS-CoV-2 isolates [329][330][331], whereas another study with recombinant SARS-CoV-2 carrying the specific point mutations reported smaller effects on nAb titers against infectious SARS-CoV-2 [332]. E484K, N501Y, and K417N escape is alarming because of the dominance of class I and II nAbs among the vaccine-or natural infection-induced polyclonal nAb responses targeting the receptor-binding ridge of RBD including sites 417, 484, and 501 [325,333,334]. As shown for P.1 variants in Brazil, VOCs may also facilitate coinfections with different SARS-CoV-2 lineages [335].…”
Section: Sars-cov-2 Mutates On a Low But Constant Level Yielding Mutant Variants Over Timementioning
confidence: 99%